Pengaruh Pemberian Ekstrak Kulit Buah Rambutan (Nephelium lappaceum L.) terhadap Penurunan Kadar Trigliserida pada Tikus Putih (Sprague dawley) Model Obesitas - Diela Gista Arvanda; Lisdiana (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to determine the effect of rambutan peel extract on triglyceride levels in Sprague Dawley obese rats. This study uses experimental laboratory research with a randomized posttest control group design. The population used in this study consisted of healthy male Sprague Dawley white rats aged 6–8 weeks, with an initial body weight of 160–200 grams and no physical abnormalities. Twenty-five Sprague Dawley rats were divided into five treatment groups, namely the control group (K-), the obesity group (K+), the Ellagic acid-induced group (T1), the RPE 15 mg/kgBW dose group (T2), and the RPE 30 mg/kgBW dose group for 30 days. Triglyceride levels were analyzed using one-way ANOVA and Tukey HSD post hoc test. The results showed that rambutan peel extract had a significant effect on triglyceride levels. The 15 mg/kgBW dose group showed a more effective reduction compared to other doses. It can be concluded that rambutan peel extract has the potential to reduce triglyceride levels in obese rats.